PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH BERBASIS PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS X MAN LABUHANBATU - Malvira Pohan; Khairuddin E. Tambunan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract:   This study aims to develop economics teaching materials using the Make A Match learning model based on Problem Solving and to test its feasibility, practicality, and effectiveness in improving the learning outcomes of class X students of MAN Labuhanbatu. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were class X students with a sample of class X-G as the experimental class and X-I as the control class. Data collection techniques were carried out through observation, questionnaires, documentation, and tests (pre-test and post-test). The results of the study showed that the developed teaching materials were classified as very feasible with an average validation of ± 87%, and very practical based on the use test by students. From the aspect of effectiveness, there was a significant increase in learning outcomes, indicated by an average pre-test score of 57.33 increasing to 89.33 in the post-test, and an N-Gain value of 0.742 (high category). The results of the Independent Sample T-test showed a significant difference between the experimental class and the control class. Thus, teaching materials based on the Make-A-Match model integrated with problem-solving are effective in improving students' economics learning outcomes and encouraging active, collaborative, and meaningful learning. Keywords: Open-Ended Materials, Make-A-Match, Problem-Solving, Learning Outcomes Abstrak: Penelitian ini bertujuan untuk mengembangkan bahan ajar ekonomi menggunakan model pembelajaran Make A Match berbasis Problem Solving serta menguji kelayakan, kepraktisan, dan keefektifannya dalam meningkatkan hasil belajar siswa kelas X MAN Labuhanbatu. Jenis penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah siswa kelas X dengan sampel kelas X-G sebagai kelas eksperimen dan X-I sebagai kelas kontrol. Teknik pengumpulan data dilakukan melalui observasi, angket, dokumentasi, dan tes (pre-test dan post-test). Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan tergolong sangat layak dengan rata-rata validasi sebesar ±87%, serta sangat praktis berdasarkan uji penggunaan oleh siswa. Dari aspek keefektifan, terjadi peningkatan hasil belajar yang signifikan, ditunjukkan oleh rata-rata nilai pre-test sebesar 57,33 meningkat menjadi 89,33 pada post-test, serta nilai N-Gain sebesar 0,742 (kategori tinggi). Hasil uji independent sample t-test menunjukkan adanya perbedaan signifikan antara kelas eksperimen dan kelas kontrol. Dengan demikian, bahan ajar berbasis model Make A Match terintegrasi Problem Solving efektif dalam meningkatkan hasil belajar ekonomi siswa serta mendorong pembelajaran yang aktif, kolaboratif, dan bermakna. Kata Kunci: Bahan Ajar, Make A Match, Problem Solving, Hasil Belajar